2015
DOI: 10.1186/s13643-015-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Australian Aboriginal and Torres Strait Islander-focused primary healthcare social and emotional wellbeing research: a systematic review protocol

Abstract: BackgroundResearch with a focus on Aboriginal and Torres Strait Islander Australian’s (hereafter referred to as Indigenous1) needs is crucial to ensure culturally appropriate evidence-based strategies are developed to improve health. However, concerns surrounding this research exist, arising from some previous research lacking community consultation, resulting in little community benefit or infringing on important cultural values. Values and Ethics: Guidelines for Ethical conduct in Aboriginal and Torres Strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The methods used in this review are previously published 13,19 , and are in accordance with PRISMA and MOOSE guidelines. This study is registered with PROSPERO (CRD42015024994).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods used in this review are previously published 13,19 , and are in accordance with PRISMA and MOOSE guidelines. This study is registered with PROSPERO (CRD42015024994).…”
Section: Methodsmentioning
confidence: 99%
“…We identified when authors reported, or we identified actions taken relating to, the values detailed in Values and ethics using a previously developed list of potential actions 13 and local protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were extracted using data extraction forms developed for this review. In accordance with our protocol 12 , we assessed risk of bias using adapted versions of existing risk-of-bias assessment tools. Studies using mixed methods were assessed according to the dominant method used.…”
Section: Discussionmentioning
confidence: 99%
“…A protocol for this review has been published previously 12 , and is in accordance with PRISMA and MOOSE guidelines. This study is registered with PROSPERO (CRD42015024994).…”
Section: Methodsmentioning
confidence: 99%